2002
DOI: 10.1038/sj.ejcn.1601458
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgery enteral nutrition in head and neck cancer patients

Abstract: Objective: Patients with head and neck cancer undergoing surgery have a high incidence of postoperative complications. The aim of our study was to investigate whether postoperative nutrition of head and neck cancer patients, using an arginineenriched diet, could improve nutritional variables as well as clinical outcomes. Design: Randomized clinical trial. Setting: Tertiary care. Subjects: A population of 47 patients with oral and laryngeal cancer were enrolled. Interventions: At surgery patients were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
1
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 16 publications
1
60
1
7
Order By: Relevance
“…Other studies have shown that arginine increased lymphocytic interleukin-2 production by macrophages . There is evidence suggesting that enteral nutrition, supplemented with different agents including arginine and dietary fiber, improve immune function and reduce postoperative complications, in head and neck cancer patients (Van Bokhorstde van der Schueren et al, 2001) (De Luis et al, 2002). Our group (De Luis et al, 2003) did not find influence on interleukins blood levels with an arginine-enhanced enteral formula in a randomized clinical trial with two intervention groups.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Other studies have shown that arginine increased lymphocytic interleukin-2 production by macrophages . There is evidence suggesting that enteral nutrition, supplemented with different agents including arginine and dietary fiber, improve immune function and reduce postoperative complications, in head and neck cancer patients (Van Bokhorstde van der Schueren et al, 2001) (De Luis et al, 2002). Our group (De Luis et al, 2003) did not find influence on interleukins blood levels with an arginine-enhanced enteral formula in a randomized clinical trial with two intervention groups.…”
mentioning
confidence: 62%
“…There is evidence suggesting that enteral nutrition, supplemented with immunomodulatory agents including arginine, improve immune function and reduced postoperative complications, in head and neck cancer patients (Riso et al, 2000;Van Bokhorst-de van der Schueren et al, 2001;De Luis et al, 2002).…”
mentioning
confidence: 99%
“…There is evidence suggesting that enteral nutrition, supplemented with different agents, including arginine and dietary fiber, improve immune function and reduce postoperative complications in different groups of patients such as pancreatic surgery , surgery of stomach and colo-rectal cancer (Gianoti et al, 1999;Wu et al, 2001), and critically ill patients (Caparros et al, 2001). In a previously randomized clinical trial, our group has demonstrated a decrease in local complications of postsurgical patients with head and neck cancer (de Luis et al, 2002). In this study, differences in formulas were arginine and dietary fiber, and perhaps fiber had a role in the detected differences.…”
Section: Introductionmentioning
confidence: 99%
“…This was similar to findings in study, which revealed most pain in cancer can be controlled by pharmacological treatment with orally administered analgesics, either alone or supplemented with co-analgesic (adjuvant) drugs. 26,27 Other short term effects caused by chemoradiotherapy and surgery were treated appropriately using drugs. And most of the patients presented with more than one side effect at a given point of time, and treatment of which led to polypharmacy which accounted upto a total of 580 prescriptions of adjuvant drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar in contrast to study by, insufficient calorie intake leading to malnutrition and loss of weight in patients with oral cancer. [23][24][25][26] The NSAIDS/ opioids was prescribed to many patients, who complained of different types of pain (79%) like tongue pain, mouth pain, pain when swallowing, pain in the palate, burning mouth, gingival pain and pain when chewing. Therefore to relieve pain, systemic drugs (12.76%) like tramadol, paracetamol, aspirin and severe pain morphine was prescribed in our study.…”
Section: Discussionmentioning
confidence: 99%